Guidance And Counseling Teachers' Strategies in Preventing Bullying in Junior High Schools - Salfiadis Salfiadis; Hizir Hizir; Ismail Ismail; Rahmat Saleh (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
Bullying in physical, verbal, or social forms negatively impacts students’ mental health and academic success, necessitating systematic prevention efforts. This study aims to describe the strategies used by Guidance and Counseling (BK) teachers to prevent bullying at Simeulue Tengah State Junior High School (SMP). The research adopted a qualitative approach with a case study design conducted over three months, from August to October 2025. Data were gathered through interviews, observations, and documentation involving six key informants, including BK teachers and student council (OSIS) administrators, supported by school records. The results indicate that BK teachers combat bullying through awareness campaigns about its negative effects during student admissions, OSIS activities, religious programs, and extracurricular events. They also offer personal and persuasive counseling to both victims and perpetrators while promoting the values of togetherness, tolerance, cooperation, and the courage to report. Additionally, student and OSIS involvement is vital in maintaining a safe and inclusive school environment. This collaborative approach involves principals, teachers, students, and OSIS members to foster a positive, violence-free school climate. The study concludes that sustainable bullying prevention is achievable through collaboration, policy integration, and nurturing positive values within the school community.